Analisis Deiksis Eksofora dalam Dialog Film 172 Days Karya Nadzira Shafa : Sebuah Kajian Pragmatik - Jumarni Jumarni; Andi Tenri Sua; Andi Srimularahmah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to describe the forms and types of exophore deixis found in the dialogue of the film 172 Days by Nadzira Shafa. This study is based on the importance of exophore deixis as an indicator element that connects language with the context of the speech situation, thus playing a role in the formation of meaning and cohesion of the film's discourse. The method used in this study is descriptive qualitative by analyzing dialogue excerpts in the film that are classified based on the theory of exophore deixis according to Purwo (1984) which includes personal deixis, spatial deixis, and temporal deixis. The results of the study show that in the dialogue of the film 172 Days there are 126 exophore deixis data which are divided into three main types, namely personal deixis, spatial deixis, and temporal deixis. 65 data of personal deixis were found which include various forms of first person pronouns (such as I, me, we, and us), second person (such as you, you, and you), and third person (such as he and they). Spatial deixis consists of 27 data in the form of place and direction indicators (such as here, there, that, and over there). A total of 34 instances of temporal deixis were found, including indicators of past time (e.g.,